1990
DOI: 10.1002/jsfa.2740530213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of egg and egg white content of food products by means of immunochemical assessment of ovalbumin

Abstract: The content of eggs and egg white, respectively, in various foods (pastes, mayonnaises, dressings, confections containing egg white, various ready-tocook mixtures, ice creams, omelettes, custards, pie Jillings etc) was assessed by radial immunodiffusion and preferably by rocket immunoelectrophoresis. The problem of partial ovalbumin denaturation during processing of dried eggs or egg white was overcome by using these products for the calibration of the method used. The method may also be applied to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…On the other hand, it was also observed, that neither the electrophoretic behavior nor peak intensity of this protein changed using middle to low temperatures from 25 to 807C, the latter corresponding to the maximum temperature typically used for pasteurization. Although it has been shown that the dissolution pH has some effect on the thermal denaturation of egg-white proteins [71], our results indicate that the procedure based on CE-MS can be less influenced by thermal degradation than those procedures based on antigen-antibody reactions [69,70,72]. Moreover, although the sensitivity provided by immunodiagnostic techniques is in general better than those one obtained by CE-MS, some other aspects, like the longer analysis times usually required for these immunotests (typically hours for ELISA vs. 30 min for CE-MS) and the risk of obtaining false positives due to cross reactions, have also to be kept in mind.…”
Section: Ce-ms Of Proteins In Food Analysiscontrasting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, it was also observed, that neither the electrophoretic behavior nor peak intensity of this protein changed using middle to low temperatures from 25 to 807C, the latter corresponding to the maximum temperature typically used for pasteurization. Although it has been shown that the dissolution pH has some effect on the thermal denaturation of egg-white proteins [71], our results indicate that the procedure based on CE-MS can be less influenced by thermal degradation than those procedures based on antigen-antibody reactions [69,70,72]. Moreover, although the sensitivity provided by immunodiagnostic techniques is in general better than those one obtained by CE-MS, some other aspects, like the longer analysis times usually required for these immunotests (typically hours for ELISA vs. 30 min for CE-MS) and the risk of obtaining false positives due to cross reactions, have also to be kept in mind.…”
Section: Ce-ms Of Proteins In Food Analysiscontrasting
confidence: 63%
“…Immunochemical methods [60,72] or classical gel electrophoresis [78] have been mainly developed to detect these contaminations/adulterations. However, the mentioned drawbacks of immunochemical tests (long analysis times, risk of false positives, strong effect of the thermal treatment) and those of classical gel electrophoresis (labor-intensive, low sensitivity) make necessary the development of new analytical protocols.…”
Section: Ce-ms Of Proteins In Food Analysismentioning
confidence: 99%
“…Diffusion-in-gel methods, such as radio-immunoelectrophoresis (RIE) and cross-radio-immunoelectrophoresis (CRIE), were the first methods to be used in the study of egg allergens. They led to the egg content analysis of various processed food products including pastes, mayonnaises, ready-to-cook mixtures, ice creams, and pie fillings and allowed the investigation of the clinical importance of ovalbumin and ovomucoid as major egg allergens , , . However, their lack of practicality for the food industry, as well as their low sensitivity, led to the preferential use of immunoenzymatic techniques such as ELISA.…”
Section: Egg Allergy and Industrial Perspectivesmentioning
confidence: 99%
“…According to the reference method, alcoholic strength of highly viscous spirits is determined by the density of a distillate using pycnometry . The content of total sugar can be analyzed chromatographically, enzymatically, or by a redox titration (back-titration after reaction with Cu 2+ as oxidizing agent), and for the content of egg yolk, several characteristic indicator substances can be used, such as cholesterol or phosphorus compounds such as phospholipids or specific egg proteins. , Given its relatively constant content (on average 12.5 mg/g egg yolk), cholesterol presents a frequently used compound to quantify the egg yolk content . It can, for instance, be analyzed enzymatically subsequent to saponification…”
Section: Introductionmentioning
confidence: 99%